JUDICIAL INDEPENDENCE: UNCONSTITUTIONAL APPOINTMENT AND DISMISSAL OF CONSTITUTIONAL COURT JUDGES - Sri Rahayu,; Naswar, Naswar; Andi Syahwiah A. Sapiddin,; Amirullah, Amirullah (Journal of Innovation Research and Knowledge, 2025)
An independent judicial system improves the quality of justice. The Constitutional Court tests laws against the constitution and has invalidated many laws of the House of Representatives. The research method employed is the normative juridical approach, formulated and advanced following theoretical principles. Normative juridical research methods primarily focus on data collecting through literature-based investigations, utilising materials accessible in libraries, archives, and other databases. Normative legal research mainly involves the examination and analysis of secondary data Judges are appointed by the DPR, the Supreme Court and the President. This article explores the dismissal and appointment of constitutional judges for the sake of judicial independence. Former Constitutional Court judges Akil Mochtar and Patrialis Akbar were replaced. Both were dismissed as Constitutional Court judges for committing corruption. In contrast, Constitutional Judge Aswanto is law-abiding. The DPR, which considers the judge, has canceled many legal products made by the DPR. The unconstitutional actions of the DPR and the president undermined the division of power between the legislature, executive and judiciary and undermined the independence of the constitutional court.